Model Pembelajaran Al Qur’an Hadis Materi Huruf Hijaiyah Pada Siswa Speech Delay Kelas 1 Mi Darul Hikmah Sidoarjo - Arofah Tis’ina, Nur (Universitas Yudharta Pasuruan, 2023)
Children's communication skills start from the reaction to the sound or voice of their father's mother, even at the age of 2 months the child can show a social smile to everyone to interact. At the age of 18 months, children begin to be able to understand and express 20 meaningful words. Starting at the age of 2 years began to be able to say 1 sentence consisting of 2 words